Effects of Iron Deficiency Anemia and Its Rapid Correction on the Serum Metabolomic Profile of Rhesus Infants. (29th May 2020) - Sandri, Brian; Lubach, Gabriele; Lock, Eric; Georgieff, Michael; Kling, Pamela; Rao, Raghavendra
Abstract: Objectives: To determine whether rapid correction of iron deficiency using intramuscular iron dextran normalizes serum metabolomic changes in a nonhuman primate model of iron deficiency anemia (IDA). Methods: Blood was collected from naturally iron-sufficient (IS; n  = 10) and IDA ( n  = 12) male and female infant rhesus monkeys ( Macaca mulatta ) at 6 months of age. IDA infants were treated with intramuscular injections of iron dextran, 10 mg/weekly for 4–8 weeks. Iron status was reevaluated following treatment using hematological measurements and sera were metabolically profiled using HPLC/MS with isobaric standards for identification and quantification. Results: Early-life iron deficiency anemia negatively affects many cellular metabolic processes, including energy production, electron transport, and oxidative degradation of toxins. Slow iron repletion with dietary supplementation restores iron deficient monkeys from a hematological perspective, but the serum metabolomic profile remains differed from monkeys that had been iron sufficient their entire life. Whether rapid iron restoration through intramuscular injections of iron dextran normalizes serum metabolomic profile is not known. A total of 654 metabolites were measured with differences in 53 metabolites identified between IS and IDA monkeys at 6 months ( P  0.05). Pathway analyses provided evidence of altered liver function, hypometabolic state, differential essential fatty acid production, irregular inosine and guanosine metabolism, and atypical bile acid production in IDA infants. After treatment, iron-related hematological parameters had recovered, but the formerly IDA infants remained metabolically distinct from the IS infants, with 225 metabolites differentially expressed between the groups. Conclusions: As with slow iron repletion, rapid iron repletion does not normalize the altered serum metabolomic profile in rhesus infants with IDA, suggesting the need for iron supplementation in the pre-anemic stage. Funding Sources: National Institutes of Health.